Panton Valentine leukocidin in MRSA strains isolated from patients at the University Hospital of Maracaibo - Romero A. Sonia; Maribel Castellano G.; Messaria Ginestre P.; Armindo Perozo M. (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Staphylococcus aureus is an increasingly important pathogen, due to the arsenal of virulence factors which presents, in addition to its high capacity to generate antimicrobial resistance. The objectives of this research were: confirm methicillin resistance by amplification the mecA gene and the presence of genes that encode Panton Valentine leucocidin (PVL) virulence factor. These genes have been investigated using polymerase chain reaction (PCR). All isolates showed the mecA gene, 50% of these strains were carrying the gene for PVL. 54,17% of the samples from pediatric patients, yield positive for this leukocidin. The highest percentage of isolation was found in samples of skin and soft tissues (85.7%).